The The Contested Mediterranean. Temporalities of New Forms of Migration Containment in Italy During the COVID-19 Pandemic - Caja, Emilio (Italian Sociological Review, 2024)
With the outbreak of Covid-19, attention has been increasingly given to new forms of confinement, both in reception facilities and detention centres. In this context, emerging forms of immigration containment and detention have initially been analysed mostly through spatial lenses. In particular, in Italy, new forms of migration containment, the so-called ‘quarantine ships’, have been analysed mostly on their spatial features: in the middle of the sea, far away from the space of the “national polity”. Yet, throughout the two years of existence of quarantine ships, attention has been drawn to the temporal dimension of this new form of migration containment. In this sense, moving beyond the analysis of quarantine ships as a static and unique form of containment, and including the ships into a broader picture that takes into consideration what happens before and after them, the article aims at understanding how new spatio-temporal regimes of control affect asylum seekers’ lives. In particular, it studies how quarantine ships have become a central device of a specific temporal regime of migration control that developed with the outbreak of Covid-19; what the connections between this regime and pre-pandemic containment configurations are; and, finally, what tactics of resistance have been put in place by asylum seekers and those acting in solidarity with them. Quarantine ships and the temporal governance strategy that developed around them (the “detention-deportation chain”) can be better understood looking at the increasing logistification of asylum seeking. On the other hand, within this emerging form of government, asylum seekers and those acting in solidarity with them put in place tactics of resistance to interrupt the suspended time imposed by this regime; to interrupt sudden accelerations, as in the case of deportations; and, finally, through practices of active memory, they challenged the status quo imposed by the EUropean border regime.